Retrievals of water vapour and temperature exploiting the far-infrared: application to aircraft observations in preparation for the FORUM mission - S. Panditharatne; S. Panditharatne; S. Panditharatne; H. Brindley; H. Brindley; C. Cox; R. Siddans; R. Siddans; J. Murray; J. Murray; L. Warwick; S. Fox (Atmospheric Measurement Techniques, 2025)
We present the extension of the Rutherford Appleton Laboratory (RAL) Infrared Microwave Sounding (IMS) optimal estimation retrieval scheme to include the use of far-infrared channels in preparation for the upcoming Far-infrared Outgoing Radiation Understanding and Monitoring (FORUM) mission. The IMS code has been previously applied to mid-infrared spectral radiances measured by the Infrared Atmospheric Sounding Instrument (IASI) to retrieve temperature and water vapour. Given this, the evolution and evaluation of the extended scheme is performed in two steps. First, clear-sky retrievals of temperature and water vapour are performed on IASI and FORUM simulations. Comparable retrieval biases are observed for retrievals of temperature and water vapour; however, there is an increase of ∼ 1 degree of freedom for water vapour and temperature for the FORUM configuration. Secondly, radiances observed from an aircraft flight in the upper troposphere are modified to match the FORUM spectral characteristics. Retrievals from these radiances using the modified code show a strong agreement with contemporaneous in situ measurements of the atmospheric state, reducing the root-mean-square error (RMSE) by 18 % for water vapour from the a priori, giving confidence in its performance. The extended IMS scheme is now available for use on FORUM observations and can be easily adapted to other far- and mid-infrared instrument configurations.